Statin-dye conjugates for selective targeting of KRAS mutant cancer cells - Hye-ran Moon; Zhenying Cai; Bo Kyung Cho; Hyeyoun Chang; Seung Taek Hong; Jean J. Zhao; Ick Chan Kwon; Thomas M. Roberts; Bumsoo Han; Ju Hee Ryu (PLoS ONE, 2026)
Over 90% of pancreatic ductal adenocarcinoma (PDAC) patients involve KRAS mutations ( KRAS MUT ), for which current treatment options are limited. Statins, commonly used to lower cholesterol, have demonstrated certain selective toxicity towards KRAS -transformed cells, prompting the question of whether statin-based conjugates could achieve selective uptake specifically in KRAS MUT cells. To investigate this, we synthesized statin-dye conjugates by attaching a fluorescent dye (Cy5.5) to two statins: simvastatin and pravastatin, aiming to assess whether selective uptake indeed occurs. Our findings revealed that these conjugates exhibited markedly enhanced uptake in KRAS MUT cells compared to KRAS wild-type ( KRAS WT ) cells. We evaluated the uptake of these conjugates in both KRAS MUT and KRAS WT cells and examined their potential to selectively target KRAS MUT pancreatic cancer cells (PCCs) using an engineered PDAC tumor model co-cultured with PCCs and cancer-associated fibroblasts (CAFs). Our findings indicate that KRAS MUT cancer cells exhibited higher uptake of statin-Cy5.5 conjugates via enhanced macropinocytosis compared to KRAS WT cancer cells and CAFs. We also found enhanced uptake of the statin-Cy5.5 conjugate in MCF10A cells with PTEN deficiency, a condition known to elevate macropinocytosis, compared to control MCF10A cells with wild-type PTEN . Notably, in the PCC and CAF co-culture model, the pravastatin-Cy5.5 conjugate selectively killed KRAS MUT PCCs without affecting the KRAS WT CAFs. These findings highlight the unique synergistic potential of statin-Cy5.5—distinct from either component alone—as targeted delivery vehicles for KRAS MUT cancer therapy.